Terrorism activities influence on financial stock markets: an empirical evidence from United Kingdom, India, France, Pakistan, Spain and America - Omar Masood; Kiran Javaria; Yelena Petrenko (Insights into Regional Development)
The aim of this study is to investigate the impact of terrorism activities on five developing and developed economies and their financial markets. Five countries selected for analysis include Spain, United Kingdom, India, Pakistan, United States of America and France. The variables under consideration are terrorism activities and market return of the financial stock markets. This study contains time series data collected on daily basis from 1st Jan 2001 to 31st Dec 2018. Study utilized deductive research approach with quantitative data. A linear regression model is used to estimate the effect of terrorist activities on the market return of the financial stock markets of the selected countries. The results of the model suggest that the market return is very much affected by the occurrence of such terror events and the model is overall statistically significant. The results of this study are consistent with the results of Freytag et al. (2009) and Bas et al., (2017) studies which show that there is significant influence of terrorism activities on financial stock market of five selected countries. This study is very significant and essential for investors and analysts as it helps them to understand how terror factors influence stock market and the right time to invest or exit the market. Findings of the study highlight and explain how terrorism activities influence the overall market return.